2021
DOI: 10.1002/hec.4439
|View full text |Cite
|
Sign up to set email alerts
|

Re‐exploring the early relationship between teenage cigarette and e‐cigarette use using price and tax changes

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…In as-yet unpublished work, Mathios 45 reports that when faced with increased ENDS price, users immediately choose cigarettes rather than quitting ENDS. Among adolescents, Pesko and Warman 19 report a significant positive association between ENDS cartridge price and number of cigarettes smoked, while other outcomes in this study and in Cantrell et al 46 did not reach statistical significance. Findings in this narrative summary are directionally consistent with Cotti et al 22 and Stein et al 47 in the meta-analysis in Figure 3, but not with the other studies in the meta-analysis, some of which were published earlier in 2016 and 2017.…”
Section: Cross-price Elasticity Of Cigarettes With Respect To Ends Pricecontrasting
confidence: 67%
See 2 more Smart Citations
“…In as-yet unpublished work, Mathios 45 reports that when faced with increased ENDS price, users immediately choose cigarettes rather than quitting ENDS. Among adolescents, Pesko and Warman 19 report a significant positive association between ENDS cartridge price and number of cigarettes smoked, while other outcomes in this study and in Cantrell et al 46 did not reach statistical significance. Findings in this narrative summary are directionally consistent with Cotti et al 22 and Stein et al 47 in the meta-analysis in Figure 3, but not with the other studies in the meta-analysis, some of which were published earlier in 2016 and 2017.…”
Section: Cross-price Elasticity Of Cigarettes With Respect To Ends Pricecontrasting
confidence: 67%
“…These were excluded from the meta-analysis model because they used different outcome measures (e.g., prevalence), non-comparable populations (e.g., adolescents or adult subpopulations), or because exact elasticities were not reported. Consistent with the metaanalysis in Figure 2, Snider et al 37 , Pesko et al 38 , Pesko and Warman 19 , and Friedman and Pesko 39 suggest that higher cigarette price is associated with significantly increased number of ENDS purchased and increased ENDS use prevalence. Cotti et al 40 and Pesko et al 41 find negative cross-price elasticity of ENDS with respect to cigarettes, however these results did not reach statistical significance.…”
Section: Cross-price Elasticity Of Ends With Respect To Cigarette Pricesupporting
confidence: 55%
See 1 more Smart Citation
“…36 Please see Section 2 for a review. Of 13 studies in total assessing the relationship between e-cigarettes and cigarettes, we document 10 studies finding they are substitutes (Pesko, Courtemanche, and Maclean 2020, Friedman and Pesko 2022, Saffer et al 2020, Pesko and Warman 2022, Friedman 2015, Pesko Hughes, and Faisal 2016, Dave Feng, and Pesko 2019, Pesko and Currie 2019, and Tuchman 2019, one study finding they are largely unrelated goods (though some evidence of substitution is present) (Allcott and Rafkin 2021), and two studies finding they are complements Adams 2017 andTefft 2018).…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies have found or supported the view that among youths and young adults, vaping acts as a substitute for cigarette smoking. 5–8 However, the degree of substitution also depends on government regulations on vaping such as whether nicotine is permitted in vaping devices, maximum permissible nicotine content, minimum age for purchase and tax on e-cigarettes, as well as the regulatory and taxation environment for cigarettes. To date, to the best of our knowledge, no studies have examined the impact of vaping introduction on cigarette smoking across settings with varied regulatory approaches to vaping.…”
Section: Introductionmentioning
confidence: 99%